Bridging the gap between branding and sustainability by fostering brand credibility and brand attachment in travellers’ hotel choice - Rosli, Nadzirah; Che Ha, Norbani; Ghazali, Ezlika Mohd (Emerald, 2019)
Purpose: This paper aims to investigate the effects of hotels’ brand attributes on consumers’ (patrons’ and guests’) by fostering brand credibility and brand attachment towards the propensity of word-of-mouth. The study uses the signaling theory to assess the relationships among the constructs. Design/methodology/approach: The study adopts partial least squares structural equation modelling (PLS-SEM) approach to validate the research model and the research hypotheses. To test the hypotheses, 474 travellers in Malaysia were recruited. Findings: The empirical results reveal that hotel attributes have direct influence on brand credibility and brand attachment. Similarly, brand credibility has direct influence on brand attachment, while brand attachment also has direct influence on word-of-mouth. Consumers’ brand credibility partially mediates the relationship between hotel attributes and brand attachment. Likewise, consumer’s brand attachment also partially mediates the relationship between hotel attributes and word-of-mouth. Last but not least, brand credibility and brand attachment sequentially mediate the relationship between hotel attributes and word-of-mouth. The theoretical and practical implications of this study are discussed together with its limitation and future research direction. Originality/value: First, in terms of measures, brand attachment construct is operationalised as a formative second-order construct, with three reflective variables (brand passion, self-brand connection and brand affection) as the first-order constructs. In addition, brand credibility is also operationalised as a formative second-order construct, with three reflective variables (expertise, trustworthiness and attractiveness) as the first-order constructs. On the other hand, hotel attributes construct is operationalised formatively as a higher-order abstraction of three categories of hotel facilities, which were also operationalised formatively (essential, culture compliant and in-room facilities). Second, this paper offers new insight into how brand credibility and brand attachment influence the relationship between hotel attributes and word-of-mouth. In a sustainability era, dissemination of complete and correct information is vital, to ensure consumers’ acceptance (e.g. likelihood to recommend to others). Thus, it is suggested that hotel managers to pay close attention to the role of brand credibility and brand attachment in tourists’ hotel choice, to secure sustainable brand. © 2019, Emerald Publishing Limited.